Penerapan Model Pembelajaran PJBL Untuk Keefektivitas Belajar Pada Mata Pelajaran SBDP - Suryandika, Ade Eka; Muzakki Jamil, Achmad; Wijayanto, Wasis (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the implementation of the Project Based Learning model in improving creativity and student learning outcomes in the Arts and Crafts (SBDP) subject. Project Based Learning is used to create a conducive learning environment by directing students in project activities that encourage collaboration, problem solving, and the development of social skills. This study uses a qualitative method with a case study approach. This research was conducted on October 14, 2024, odd semester of the 2023/2024 academic year. The primary sources in this study are: class teachers. While the secondary data in this study are: books, and scientific articles related to the research. In data collection techniques, researchers use observation techniques. The results of the study indicate that the implementation of Project Based Learning is able to create learning effectiveness and improve creativity and student learning outcomes. This study shows that Project Based Learning is not only effective in learning but also plays a role in improving creativity and student learning outcomes. Therefore, it is recommended to implement Project Based Learning as an effective learning method at the elementary school level to create a more meaningful learning experience.